Impact of inferior vena cava entry characteristics on tricuspid annular access during transcatheter interventions. Issue 4 (27th January 2022) - Ranard, Lauren S.; Vahl, Torsten P.; Chung, Christine J.; Sadri, Shirin; Khalique, Omar K.; Hamid, Nadira; Nazif, Tamim; George, Isaac; Ng, Vivian; Patel, Amisha; Rezende, Carolina P.; Reisman, Mark; et al.
Abstract: Objectives: The purpose of this study was to characterize the anatomic relationship between the inferior vena cava (IVC) and tricuspid annulus (TA) and its potential impact on the performance of transcatheter TV interventions. Background: Transcatheter tricuspid valve (TV) interventions are emerging as a therapeutic alternative for the treatment of severe, symptomatic tricuspid regurgitation (TR). Progression of TR is associated with right heart dilatation. These anatomic changes may distort the IVC–TA relationship and impact successful implantation of transcatheter devices. Methods: Fifty patients who presented with symptomatic TR for consideration of transcatheter TV therapy with an available CT were included in the study. Comprehensive transesophageal echocardiogram and CT analyses were performed to assess the right‐sided cardiac chambers, TA and IVC–TA relationship. Results: The mean age of the study cohort was 78.4 ± 8.9 years. Torrential TR was present in 54% ( n  = 27). There was considerable variation in the short axis mid‐IVC to mid‐TA offset (SAXMID 18.2 ± 7.9 mm, range 4.7–42.1 mm). Conclusions: The IVC‐to‐TA relationship exhibits significant variability in patients with symptomatic TR. CT analysis of the tricuspid anatomy, including the relationship to the surrounding structures and the IVC, is essential for planning transcatheter TV interventions. Further studies are needed to define whether the IVC‐to‐TA relationship is a predictor of technical success in the context of specific transcatheter delivery systems.